Value devolution in social enterprises: Institutional economics and systems theory perspectives - Vladislav Valentinov (Administration & Society, 2015)
Agafonow's article locates the role of social enterprises in devolving value through output maximizing behavior. This short paper embeds Agafonow's argument in the societal and institutional context by building upon Luhmann's social systems theory. According to Luhmann, the functional system of the economy exhibits “imperatives” that cause social ills. The institutional form of social enterprises is shown to weaken these imperatives in several ways. One of these ways, discussed by Agafonow, is the substitution of profit maximization by output maximization. Other ways are the substitution of high-powered incentives by low-powered ones as elaborated in the work of Williamson and Hansmann.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; value devolution; social enterprises; Niklas Luhmann; Oliver Williamson; Henry Hansmann